2020
DOI: 10.3390/nu12082464
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zinc in Selected Female Reproductive System Disorders

Abstract: Zinc is an essential microelement that plays many important functions in the body. It is crucial for the regulation of cell growth, hormone release, immunological response and reproduction. This review focuses on its importance in the reproductive system of women of reproductive and postmenopausal ages, not including its well described role in pregnancy. Only recently, attention has been drawn to the potential role of zinc in polycystic ovary syndrome (PCOS), dysmenorrhea, or endometriosis. This review is main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 108 publications
2
56
0
3
Order By: Relevance
“…This was shown in a study that found that zinc significantly lowered the pain duration and severity in women compared to the control group and improved the patients’ quality of life [ 285 ]. One study suggested that daily intake of 30 mg of zinc one to four days prior to menstruation can prevent menstrual cramping pain, without harmful side effects, while another showed evidence that zinc can treat primary dysmenorrhea in adolescent girls [ 286 ].…”
Section: Menstrual Disordersmentioning
confidence: 99%
“…This was shown in a study that found that zinc significantly lowered the pain duration and severity in women compared to the control group and improved the patients’ quality of life [ 285 ]. One study suggested that daily intake of 30 mg of zinc one to four days prior to menstruation can prevent menstrual cramping pain, without harmful side effects, while another showed evidence that zinc can treat primary dysmenorrhea in adolescent girls [ 286 ].…”
Section: Menstrual Disordersmentioning
confidence: 99%
“…Zinc plays a role in homeostasis, cell growth, hormone release, immunological responses, and biological reproduction. It also protects cells against reactive oxygen species [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low zinc intake in obese people is associated with hyperinsulinemia, increased low-grade inflammation, and a worsened lipid profile. In addition, zinc ions can act in an insulin-mimetic manner in adipocytes, stimulating lipogenesis and glucose transport through the translocation of glucose transporter 4 (GLUT4) to the plasma membrane [ 109 ]. Zinc deficiency may play a significant role in the pathogenesis of PCOS and may be a prognostic marker of PCOS.…”
Section: Lifestyle Changesmentioning
confidence: 99%